MO956APPRAISAL OF PSYCHO-SOCIAL BURDEN AND QUALITY OF LIFE OF KIDNEY DONORS- IS THERE A DEEP ROOTEDAPPREHENSION ?. (29th May 2021) - Kaul, Anupma; Behera, Manas
Abstract: Background and Aims: Living kidney donation is a very complex psychological experience for donor candidates as well as the recipients improving self-esteem and donor-recipient relationships on one hand while may add on to emotional stresses increasing psychic vulnerability and predisposition to the development of mental disorder. The present study aimed to look into psychosocial outcome among donor characteristics and quantification of the psychological impact of kidney donation. Method: This was a retrospective random study conducted among 506 renal transplant donors from 2010 till 2018 at Department of nephrology and transplantation at a tertiary care centre in northern part of India. Results: Majority of donors were females ie mothers (38.1%) and wife (35.5%). A total of 18.6% developed one or more co morbid illness following transplantation. Most of the donors (98.9%) were motivated by affection and love for the recipient and out of them (89.1%) felt that there were the first choice among the available donors. A majority of them (94.5%) felt that donation had positively affected their relationship and were respected. These donors showed lesser degree of both depressive and anxiety (HAD score 3.5) and depressive score (BDI II 4.8). Donation had upgraded the stature of the donor in the family and recipient which proved statically significant predictor on donor related outcome. Donors well being was dependant on recepients wellbeing and 20% of the donors felt or were made to feel the guilt of the graft failure or a poor outcome. Conclusion: The study showed a positive acknowledgement for the donors from the recipients and society thus giving a meaning to life Need of the hours is greater post donation monitoring as well as due recognition among donors which can improve long term donor outcomes.